BIBLIOMETRIC UPDATE ON THE SERRANIDAE FAMILY (SWAINSON, 1839) IN THE ATLANTIC OCEAN : Atualização bibliométrica da família Serranidae (Swainson, 1839) no Oceano Atlântico - Leite Rebouças, Pedro Henrique; Nóbrega, Marcelo Francisco (Arquivos de Ciências do Mar, 2024)
The Serranidae family’s significant economic importance in the Atlantic Ocean, particularly in subtropical areas, contrasts with its ecological role as slow-growing predators, especially species that form reproductive aggregations. This contrast has led to overfishing of many species. Despite this, most studies focus primarily on the most economically important species, leaving many gaps in our understanding of the group. The aim of this article is to update the state of the scientific research of the Serranidae family in the Atlantic. We gathered data using the Scopus database with the query “TITLE-ABS-KEY (Serranidae AND Atlantic)” and filtered the results. Our findings reveal a decrease in both citation and publication rates, as well as a heavy concentration of research in the Western Atlantic, particularly in the USA. We provide an update on bibliometric data regarding scientific production, citations, international collaborations, journals, and institutions related to the Serranidae family in the Atlantic. There are significant knowledge gaps concerning species in this family, and the concentration of studies in specific areas is concerning. The threats facing groupers are numerous, and the concentration of research exacerbates the vulnerability of less-studied regions, highlighting the need for more continuous and comprehensive studies. Keywords: Groupers, review, productivity, distribution, scientometrics.